Penerapan Metode ELECTRE Dalam Penentuan Pemilihan Kartu Smartphone - Gustian Rama Putra (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2022)
The choice of a smartphone card can be an important decision because it can affect your usage experience in communicating, surfing the internet, and using other services. The ELECTRE method is very effective for MADM which has qualitative and quantitative features. The concept used in the ELECTRE method is to handle the relationship between outranking by using pairwise comparisons between existing alternatives based on each predetermined criterion. The purpose of this study is to provide recommendations to users in the selection of smartphone cards by paying attention to the criteria used. Based on the results of the ranking of housing site selection that gets rank 1, namely XL.